PENGARUH KUALITAS AUDIT TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2016 – 2018) - Endah Catur Riyanti; Hanna Christina W Putri; Wikanto Artadi; Haryono Umar (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2019)
This study aims to obtain empirical evidence the influence of Audit Quality on the Fraudulent Financial Reporting with Audit Committee as a Moderating Variable in Manufacture Companies listed in Indonesia’s Stock Exchange on 2016 – 2018. This paper uses generalised least squares regression to investigate the influence of Audit Quality on the Fraudulent Financial Reporting with Audit Committee as a moderating variable for a sample of manufacturing companies listed on Indonesia Stock Exchange over a three-year period from 2016 to 2018. The method of  purposive sampling is used to gain the samples. The measurement of FFR is using Real Earning Management (Abnormal Cashflow). Audit Quality and Audit Committee are analyzed from the data within annual report. The result of the research findings show that Competence of Audit Committee has a positive insignificant effect on Fraudulent Financial Reporting. Meanwhile Audit Quality have a negative insignificant effect on Fraudulent Financial Reporting and Audit Committee strengthens positive insignificant of Audit Quality on Fraudulent Financial Reporting. The main contribution of this study is that it investigates Audit Committee strengthens influence of Audit Quality on Fraudulent Financial Reporting on Fraudulent Financial Reporting. Furthermore, this study is the initial paper to examine the impact of Audit Quality and Audit Committee on Fraudulent Financial Reporting in Indonesia.